Alopecia areata: from immunopathogenesis to emerging therapeutic approaches - Kim, Su-Young; Lee, Hyun Joo; Heo, Jihye; Kim, Beom Joon; Seok, Joon (Frontiers in Immunology, 2025)
Alopecia areata (AA) is a non-scarring inflammatory hair loss disorder characterized by a T-cell–mediated autoimmune disease that targets the hair follicles. In particular, Natural Killer Group 2 member D (NKG2D)+CD8+ T cells have been identified as central players in its pathogenesis. Current treatment options have limited efficacy and are often associated with adverse effects and high risk of relapse upon discontinuation, highlighting the need for targeted and durable therapeutic strategies. Janus kinase (JAK) inhibitors have emerged as representative therapies; however, they are limited by a high relapse rate after treatment cessation. Recently, novel therapeutic approaches such as neutralizing antibodies targeting cytokines and chemokines, and sphingosine-1-phosphate (S1P) receptor modulators have gained attention. Various molecular markers associated with AA have been identified as potential therapeutic targets. This review provides a comprehensive overview of the roles of immune cells in AA pathogenesis and introduces emerging immunomodulatory strategies and novel therapeutic targets.